Pengadaan Tempat Sampah Sebagai Wujud Implementasi Pemilahan Sampah Berbasis Masyarakat - Ai Teti Wahyuni; Yustika Ratna Sari; Fitria Himatul Aliyah; Siti Ai Nuraeni; Mamar Mardiah; Arif Rahman Aziz (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Lack of public awareness about the importance of cleanliness of public facilities, especially worship facilities in Margacinta Village, is one of the problems that have occurred. So it is necessary to carry out an evaluation to prevent problems so that they do not cause disease later. The purpose of holding this KKN is to find solutions related to environmental problems in Margacinta Village. Some of these places are mosques in the hamlets of Margacinta Village, because of these problems. So the solution is to hold trash bins as a form of waste sorting implementation organic and non-organic in Margacinta Village. In this PKM Journal, the function of the trash can will be explained. So that this effort is expected to increase public awareness about the importance of environmental cleanliness, especially in places of worship. The method used is the direct delivery of trash bins and directing the community so they can choose and sort organic and non-organic waste. The trash bins are handed over to the head of DKM The Mosque Prosperity Council located in the hamlet. We as KKN students hope that by holding this program we can increase public awareness about the importance of environmental cleanliness in Margacinta Village so that Margacinta Village can become a cleaner and healthier village in the future.",